Edukasi K3 Dalam Penggunaan Pestisida dan APD Di Kel. Gantarang Keke, Kabupaten Bantaeng - Waode Rustiah; Nur Qadri Rasyid (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2021)
Pesticides is chemical substances and other materials as well as microorganisms and viruses that are used to control various plant-disturbing organisms. Early public education about pesticides is an important element to avoid increasing exposure for farmers or workers in the spraying division of plant pests. In addition, the community has never carried out early detection and feels that they are already immune and are used to the pungent smell of pesticides. This service activity is carried out with the aim of implementing a community-based education program that facilitates the community in increasing knowledge about early detection and preventive efforts against the using of pesticides that do not meet the requirements in the application of Occupational Health and Safety (K3) principles in Gantarang Keke Village, Bantaeng Regency. Methods of implementation this community service consists of two stages, namely: 1) the preparation stage includes health counseling with the lecture method to the community of Gantarang Keke Village; 2) the implementation stage includes the implementation of the implementation program in the form of implementing K3 correctly and safely. The results show that with education carried out through counseling about the application of K3 to the people of Gantarang Keke Village, they begin to understand about the safe and correct using of pesticides, as well as the use of Personal Protective Equipment in accordance with the requirements in K3 principles.